Supervisi, Monitoring, dan Evaluasi Pendidikan dalam Peningkatan Mutu Lembaga Formal dan Non-Formal di Pondok Pesantren Nurul Jadid Paiton Probolinggo - Ahmad Zubaidi (GUYUB: Journal of Community Engagement, 2020)
Nurul Jadid is one of the biggest Islamic boarding schools in Probolinggo Regency with many formal and non-formal educational institutions. However, some of them have a lack of supervision in maintaining their quality aspects because of some reasons, such as less qualified human resources, overlapping schedules, and administrative business. Furthermore, this program is to focus on deploying supervision, monitoring, and evaluation over formal and nonformal educational institutions in Nurul Jadid. The result of this program is first, teacher’s and student’s learning tools in MI Nurul Mun’im are relatively completed and standardized, teacher’s understanding of goals of Quranic literacy and furudhul ‘ainiyah is highly demonstrated, the process of uneven semester 2018/2019 final exam in MTs Nurul Jadid is smoothly implemented, about 95% administrative requirements for pre-accreditation in SMP Nurul Jadid is achieved, and educational process in MA Nurul Jadid is based on eight (8) criteria of National Educational Standards.